Hydatid cyst involvement of both pulmonary arteries in a 14-year-old girl - YILDIZELİ, BEDRETTİN (TAYLOR & FRANCIS LTD, 2018)
Hydatid disease is the most common mediterranean parasitic infection; it commonly affects the liver and lungs and rarely involves multiple organs. A 14-year-old girl presented with a 1-year history of dyspnoea and fatigue. She was found to have pulmonary hypertension owing to hydatid cysts in the right ventricle and both pulmonary arteries. After administration of albendazole she underwent pulmonary endarterectomy and a calcified hydatid cyst was removed from the right ventricle. She made a complete recovery and remained on albendazole for 6 months.
Keywords: Echinococcus granulosus; hydatid cyst; pulmonary hypertension; right ventricle; ECHINOCOCCOSIS